Chinese Cultural Diplomacy: instruments in China’s strategy for international insertion in the 21st Century - Danielly Silva Ramos Becard; Paulo Menechelli Filho (Revista Brasileira de Política Internacional, 2019)
Abstract This article analyzes instruments of Chinese cultural diplomacy (2003-2018), such as the media, cinema, and the Confucius Institutes, as well as its potential to overcome barriers between states. China’s cultural soft power was studied in Confucius Institutes in the U.S.. The conclusion is that China increasingly used cultural diplomacy and turned it into a key instrument in its strategy for international insertion.